Implementasi Pendampingan Kepada Tutor Kesetaraan Melalui Pendekatan Meusapat dalam Pembelajaran Berdiferensiasi pada PKBM Cerdas Mandiri - Gusti, Erwina (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2022)
This study aims to improve student learning outcomes in the subjects taught by each Smart Mandiri PKBM tutor. This study uses a differentiated approach by involving tutors and learning residents. Assistance research by the East Aceh Education office supervisor which involved the entire team involved in PKBM Cerdas Mandiri which was divided into two conditions, firstly, men and women were put together, where the two learning residents were separated by men and women by being separated by curtains or other barriers. The method used is the Meusapat method, namely the grouping between students and men separated in teaching and learning activities. It was concluded that from the number of tutors in Smart Mandiri PKBM, 81% tended to strongly agree with differentiated learning mentoring carried out by the author through a meusapat approach to increase the sense of responsibility and desire of learning residents to attend learning activities by grouping them by gender. The results of the research on Equality Tutor Assistance in Differentiated Learning through the Meusapat approach are very effective in having a positive impact on tutors in inviting learning citizens to attend teaching and learning activities. Through the Meusapat Approach, tutors are able to increase the responsibility of learning citizens to participate in equality education programs using local languages. Through this good practice, the author hopes that the CLC fostered in the East Aceh Regency environment will be more courageous in expressing the problems that occur in PKBM.